Pengukuran jarak objek pejalan kaki terhadap kamera menggunakan kamera stereo terkalibrasi dengan segmentasi objek histogram of oriented gradient - Tutur Urip; Kusworo Adi; Catur Edi Widodo (Youngster Physics Journal, 2017)
The distance measurement of pedestrian object to camera using a calibrated stereo camera has been investigated. The study was conducted by comparing Data-A and Data-B with different conditions and environment data interpretation. The stereo vision methods include camera calibration, image rectification, disparity counting, three-dimensional reconstruction and object segmentation. The object segmentation is performed using the Histogram of Oriented Gradient  feature to segment pedestrian object. Meanwhile, to determine the distance value is based on the information of the centroid of the bounding box segmented object.The calculations were performed using the Euclidian Distance calculation method to find the shortest distance between the centroid of the bounding box with both cameras. From the research results, the best accuracy was obtained  with measurement error of 4%. Keywords: Measurement object, pedestrian, calibrated stereo camera, Histogram of Oriented Gradient, Euclidian Distance.